Ochrona spoczynku nocnego w kodeksie wykroczeń jako akceptowane ograniczenie wolności - Sawicki, Janusz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article addresses one of the basic objects of protection under petty offences law that is generally applicable, namely the right of every individual to an uninterrupted night’s rest. The provisions of the Code of Petty Offences that protect night rest simultaneously limit liberty and freedom of action for people held liable for pretty offences thereunder. In order to properly assess the validity of these limitations and, concomitantly, appreciate the significance of the relevant regulations and understand the reasons for their social acceptance, the author submits the provisions of Article 51(1) and (2) of the Code of Petty Offences to a detailed analysis in relation to disturbing night rest. As part of the analysis, the most important shortcomings of the provisions are pointed out (which have been previously noted in both legal literature and judicial decisions), and de lege ferenda proposals for overcoming these shortcomings and ensuring not only the correct, but also easier application of the provisions of the Code of Petty Offences that protect night rest, are put forth
Keywords: kodeks wykroczeń; zakłócenie i ochrona spoczynku nocnego; ograniczenie wolności człowieka; społeczna akceptacja; propozycje zmian